DNA Methylation Basis in the Effect of White Matter Integrity Deficits on Cognitive Impairments and Psychopathological Symptoms in Drug-Naive First-Episode Schizophrenia - Zong, Xiaofen; Zhang, Qinran; He, Changchun; Huang, Xinyue; Zhang, Jiangbo; Wang, Gaohua; Lv, Luxian; Sang, Deen; Zou, Xiufen; Chen, Huafu; Zheng, Junjie; Hu, Maolin (Frontiers in Psychiatry, 2021)
Background: Mounting evidence from diffusion tensor imaging (DTI) and epigenetic studies respectively confirmed the abnormal alterations of brain white matter integrity and DNA methylation (DNAm) in schizophrenia. However, few studies have been carried out in the same sample to simultaneously explore the WM pathology relating to clinical behaviors, as well as the DNA methylation basis underlying the WM deficits. Methods: We performed DTI scans in 42 treatment-naïve first-episode schizophrenia patients and 38 healthy controls. Voxel-based method of fractional anisotropy (FA) derived from DTI was used to assess WM integrity. Participants’ peripheral blood genomic DNAm status, quantified by using Infinium® Human Methylation 450K BeadChip, was examined in parallel with DTI scanning. Participants completed Digit Span test, Trail Making test, as well as Positive And Negative Syndrome Scale measurement. We acquired genes that are differentially expressed in the brain regions with abnormal FA values according to the Allen anatomically comprehensive atlas, obtained DNAm levels of the corresponding genes, and then performed Z-test to compare the differential epigenetic-imaging associations (DEIAs) between the two groups. Results: Significant decreases of FA values in the patient group were located in the right middle temporal lobe WM, right cuneus WM, right anterior cingulate WM, and right inferior parietal lobe WM, while the significant increases in the bilateral middle cingulate WM (Ps<0.01, GRF correction). Abnormal FA values were correlated with patients’ clinical symptoms and cognitive impairments. In the DEIAs, patients showed abnormal couple patterns between altered FA and DNAm components, for which the enriched biological processes and pathways could be largely grouped into three biological procedures: the neurocognition, immune and nervous system. Conclusion: Schizophrenia may not cause widespread neuropathological changes, but subtle alterations affecting local cingulum WM, which may play a critical role in positive symptoms and cognitive impairments. This imaging-epigenetics study revealed for the first time that DNAm of genes enriched in neuronal, immunologic and cognitive processes may serve as the basis in the effect of WM deficits on clinical behaviors in schizophrenia.